DETERMINASI PENERAPAN SISTEM AKUNTANSI KEUANGAN DENGAN SISTEM PENGENDALIAN INTERNAL SEBAGAI VARIABEL MODERASI YANG MEMPENGARUHI KUALITAS LAPORAN KEUANGAN DAERAH - Dennyca Hendriyanto Nugroho; Febra Robiyanto (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2023)
This study aims to examine the Effect of Regional Financial Accounting System, Financial Management Transparency, and Use of Information Technology on the Quality of Regional Financial Statements with the Internal Control System as a coding variable. The data used in this study are primary data. The data collection method uses questionnaires that are distributed to respondents. The questionnaire was distributed to 64 employees of the Kudus Regency Regional Revenue, Finance and Assets Management Agency. The data analysis method used in this study is Moderated Regression Analysis (MRA). The results of this study show that the influence of the Regional Financial Accounting System has a positive and significant effect on the quality of Financial Statements, Financial Management Transparency does not have a positive and significant effect on the quality of Financial Statements. Financial Statements, and the Use of Information Technology do not have a positive and significant effect on the Quality of Financial Statements. The results of this study also show that the Internal Control System moderates the relationship between the Influence of the Regional Financial Accounting System, while the Internal Control System is unable to moderate the Influence of Financial Management Transparency, and the Use of Information Technology on the Quality of Financial Statements.